SURFACE WATER QUALITY ASSESSMENT IN SEMI-ARID REGION (EL HODNA WATERSHED, ALGERIA) BASED ON WATER QUALITY INDEX (WQI) - FERAHTIA, Amel; HALILAT, Mohammed Tahar; MIMECHE, Fateh; BENSACI, Ettayib (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The present study was aimed to assess the surface water pollution sources in a semiarid region of Algeria by characterizing the physicochemical quality of the water of the main Wadis of the El Hodna watershed and determining the water quality index according to the uses of drinking water, irrigation, and aquatic life. This index is calculated in purpose to communicate information on the water quality for concerned citizens and policymakers. The calculated WQI values of the studied Wadis were higher than 100, which indicates that the waters of the El Hodna watershed are unfit for human consumption, irrigation, and aquatic life. The obtained results have shown that different types of pollution (industrial, domestic and agricultural) affect the waters of the El Hodna watershed, which lead to degrade the water quality of this aquatic ecosystem and consequently its biodiversity and public health.